The effect of chewing gum on postoperative ileus after laparotomy for gastroduodenal perforations: a randomized controlled trial - Muhumuza, Joshua; Molen, Selamo; F.; Bassara; Godefory N.; Waziri, Musa A.; Kithinji, Stephen M.; Sonye, Kiyaka M.; Leocadie, Mugisho M.; Kagenderezo, ByaMungu P.; Tshimanga, Esperant T.; Faustin, Tatana M.; et al. (BioMed Central Ltd, 2025)
Background: Prolonged postoperative ileus is linked to a higher risk of additional complications, longer hospital stays, and higher healthcare expenses. There are few randomized controlled trials on the impact of chewing gum on the duration of ileus in patients undergoing emergency surgery, notably those with peritonitis. Compelling evidence from studies on elective procedures demonstrates that chewing gum can lessen the duration of ileus. This trial aimed to examine the effect of chewing gum on the length of the postoperative ileus which develop after laparotomy for gastroduodenal perforations.
Materials and methods: Multicentre randomized controlled trial. Fifty-two patients were randomly assigned to two treatment groups. Group A received routine care with chewing gum, while group B only received routine care. The primary outcome was the length of postoperative ileus, while the secondary outcomes were the length of hospital stay, in-hospital morbidity, and mortality. The continuous variables were compared using the nonparametric Wilcoxon Rank sum (Mann-Whitney U) test while the categorical outcomes were compared using the chi-squared test in SPSS version 26. The protocol was retrospectively registered with the WHO Pan African Clinical Trial Registry (Number: PACTR202206468032528) on the 1st of June 2022.
Results: Of the 52 participants included in the analysis, the majority were males (80.8%) with a mean age of 34.23 (SD = 11.52) years. There was no statistically significant difference in the baseline characteristics of the study participants between the two groups (P > 0.05 for all). The median duration of postoperative ileus was 21.5 h less in the chewing gum group (28.5 versus 50.0, P = 0.002), while the length of hospital stay was 2.5 days less in the chewing gum group (5.4 versus 7.9, P = 0.007). There was no significant difference noted in the occurrence of complications.
Conclusion: Chewing gum that is readily available and reasonably priced may help shorten the duration of post-operative ileus, which has the extra benefit of enabling early discharge.